Gender and Black–White Race Differences in Young Adult Exercise Dependence Prevalence and Associated Disordered Eating. Issue 4 (2nd October 2021) - MacIntyre, Rachel I.; Heron, Kristin E.; Howard, Lindsay M.; Symons Downs, Danielle
ABSTRACT: Purpose : Exercise dependence, an unhealthy preoccupation with exercise that results in physiological and psychological symptoms, may be particularly prevalent among college students given sociocultural exercise and body ideals in this population. Yet few studies have examined this phenomenon in diverse college samples. The aims of the present study were to examine gender and Black–White race differences in the prevalence of exercise dependence and associated disordered eating. Method : Undergraduates ( N = 839) completed online measures of exercise dependence and disordered eating. Chi square tests were used to test for differences in prevalence, and linear regression was used to examine race and gender moderating effects on the exercise dependence–disordered eating association. Results : More men reported exercise dependence symptoms than women. More White participants reported symptoms than Black participants. Of the four gender and race combinations examined, White men had the highest proportion and Black women the lowest proportion experiencing symptoms. Gender, but not race, moderated the exercise dependence–disordered eating association. Conclusions : Although more men experience exercise dependence symptoms, women experience stronger associations between exercise dependence symptoms and disordered eating. The number of students who reported exercise dependence symptoms underscores the need for further research in this population and the development of culturally sensitive interventions.